2012
DOI: 10.3390/ijms13056236
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Caffeic Acid on Paclitaxel Induced Anti-Proliferation and Apoptosis of Lung Cancer Cells Involves NF-κB Pathway

Abstract: Caffeic acid (CA), a natural phenolic compound, is abundant in medicinal plants. CA possesses multiple biological effects such as anti-bacterial and anti-cancer growth. CA was also reported to induce fore stomach and kidney tumors in a mouse model. Here we used two human lung cancer cell lines, A549 and H1299, to clarify the role of CA in cancer cell proliferation. The growth assay showed that CA moderately promoted the proliferation of the lung cancer cells. Furthermore, pre-treatment of CA rescues the prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 28 publications
1
27
1
Order By: Relevance
“…CA also exhibits an anti-cancer effect against human cervical carcinoma, head and neck squamous carcinoma, colon cancer, and renal carcinoma [12][13][14]26]. A previous study showed that CA promoted NSCLC A549 cell proliferation and enhanced PTX-induced proliferation inA549 cells [17], suggesting that it has the potential to facilitate A549 growth through the p53 pathway and enhance the protective effect of PTX. However, the in vivo and in vitro effects on p53 deficiency cell line H1299 and the molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA also exhibits an anti-cancer effect against human cervical carcinoma, head and neck squamous carcinoma, colon cancer, and renal carcinoma [12][13][14]26]. A previous study showed that CA promoted NSCLC A549 cell proliferation and enhanced PTX-induced proliferation inA549 cells [17], suggesting that it has the potential to facilitate A549 growth through the p53 pathway and enhance the protective effect of PTX. However, the in vivo and in vitro effects on p53 deficiency cell line H1299 and the molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the potential therapeutic efficacy and underlying mechanisms of CA in combination with PTX for the treatment of NSCLC, we used both H1299 cells and a xenograft mouse model in this study because a previous study had shown the protective effect of CA on PTX-induced cell death in NSCLC A549 cells through the NF-κB signaling pathway [17]. It was found in the previous study that high-dose CA (600 μM) significantly induces apoptosis in A549 and H1299 cells and plays a potential role in modulating and enhancing PTX-induced apoptosis of NSCLC cells both in vivo and in vitro through the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid, a natural phenolic acid compound present in fruits, wine and coffee 100 , and its synthetic derivative, CAPDE, were reported to inhibit tumour growth and angiogenesis in a renal carcinoma mouse xenograft model. Its effects are induced partly by suppressing active STAT3 and the expression of hypoxia-inducible factor 1α (HIF1α) and VEGF 101 .…”
Section: Inhibitors Of Stat3mentioning
confidence: 99%
“…Caffeic acid ( II ) showed multiple biological effects such as antidiabetic, antibacterial, antitumor, antioxidant, neuroprotective, anti-inflammatory, and antimicrobial, and it inhibited α -glucosidase (Kumar et al 2012 ;Lin et al 2012 ;Singh et al 2012 ). Cedrusin ( III ) could significantly promote the growth of Lactarius deliciosus (Gong 2008 ).…”
Section: Resultsmentioning
confidence: 99%